Cabinet Rule in the Republic of China: A Constitutional Argument - Fu, Hu (Columbia Journal of Asian Law, 1990)
Since the adoption of the Constitution of the Republic of China (Constitution) in 1946, the government of the Republic of China (ROC) has often been characterized as a “strong-man” system. This appellation implies that an individual, or “strong man,” exercises full political power over people and policies within the state. It suggests also that to a certain extent such a person is able to raise himself above the confinements of the constitutional system in the exercise of such power. For example, a president has historically enjoyed substantial powers, while a premier of the Executive Yuan has served as the president’s subordinate. This arrangement departs from constitutional provisions that establish the presidency as a nominal position with merely symbolic powers. Yet, it is this office which today retains the ultimate decision-making power and remains accountable to the Legislative Yuan.